Implementasi Kebijakan Pedoman Wisata Berkelanjutan pada Objek Wisata Air Panas Cisolong Kabupaten Pandeglang (Studi Peraturan Menteri Pariwisata dan Ekonomi Kreatif Nomor 9 Tahun 2021) - Flipins Pande Hasiholan Lumban Toruan Lumban Toruan (Epistemik: Indonesian Journal of Social and Political Science, 2026)
Sustainable tourism has become a key foundation for creating a safe and comfortable environment at the Cisolong Hot Springs tourist destination. However, visitors have expressed various concerns regarding the quality of facilities and overall comfort within the area, including damaged pool infrastructure and inadequate sanitation conditions. This study aims to examine the implementation of the Minister of Tourism and Creative Economy Regulation Number 9 of 2021 by applying the policy implementation framework proposed by Van Meter and Van Horn. The framework identifies six key variables that influence the success of policy implementation: (1) policy standards and objectives; (2) resources; (3) inter-organizational relationships; (4) characteristics of implementing agencies; (5) social, political, and economic conditions; and (6) the disposition or attitudes of policy implementers.. Based on the analysis and findings obtained in the field, the researcher concluded that the implementation of the Minister of Tourism and Creative Economy Regulation Number 9 of 2021 concerning guidelines for sustainable tourism in the Pandeglang Regency hot spring tourist attraction, which is located at the Pandeglang Regency Tourism Office, especially in the management of sustainable tourism in the Cisolong hot spring tourist attraction, is still not optimal. Keywords: Implementation, Sustainable Tourism.